Indirect bonding - do custom bases need a plastic conditioner? A randomised clinical trial - Miles Peter (Sciendo, 2023)
To compare the clinical failure rates over six months of indirectly bonded brackets with and without methyl methacrylate monomer (MMM) conditioned custom bases.